2003
DOI: 10.1034/j.1600-0773.2003.930306.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Specifically Inhibits Cytochrome C Oxidase of Human Mitochondrial Respiratory Chain

Abstract: Carbon monoxide (CO) toxicity is the result of a combination of tissue hypoxia and direct CO-mediated damage at a cellular level, since not all the signs and symptoms presented can be explained only by the formation of carboxyhaemoglobin. Mitochondria, specially the electron transport chain, seem to be the target for CO at a subcellular level. However, the direct effect of CO in individual complexes of the human mitochondrial respiratory chain has not been completely elucidated. We here studied the in vitro ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
1
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(135 citation statements)
references
References 44 publications
7
120
1
7
Order By: Relevance
“…These findings may have particular clinical significance as most of the tetrazoles, thiazoles, and 1,2,3-triazoles identified in this paper are reversible inhibitors of mitochondrial respiration. The reversibility of mitochondrial inhibition by these compounds is very important because irreversible inhibitors, such as carbon monoxide, azide, and rotenone, are wellknown metabolic poisons (16)(17)(18). In addition, many of the heterocycles described herein have low reported toxicities (19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…These findings may have particular clinical significance as most of the tetrazoles, thiazoles, and 1,2,3-triazoles identified in this paper are reversible inhibitors of mitochondrial respiration. The reversibility of mitochondrial inhibition by these compounds is very important because irreversible inhibitors, such as carbon monoxide, azide, and rotenone, are wellknown metabolic poisons (16)(17)(18). In addition, many of the heterocycles described herein have low reported toxicities (19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…One such a toxicant is carbon monoxide (CO), which is found at levels that are 2.8-fold higher in SS smoke than in MS smoke (Committee on Passive Smoking, 1986). CO inhibits the mitochondrial respiratory chain by interfering with the cytochrome c oxidase (Alonso et al, 2003) and may affect sperm motility by altering mitochondria functions and reducing the energy stores needed for motility. Ex vivo studies have shown that fully mature sperm are not susceptible to CO (Makler et al, 1993), indicating that CO may affect the acquisition of sperm motility in the epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…CO also combines with cytochrome A and A3 to cause direct poisoning effects, and decreases in levels of cytochrome C oxidase inhibit mitochondrial metabolism, leading to cellular respiratory dysfunction. 13 Furthermore, CO-mediated brain damage associated with free radicals has been noticed. CO binds to platelet heme proteins, causing the release of nitric oxide.…”
Section: Mechanisms Causing Brain Damage After Co Exposurementioning
confidence: 99%